Synthesis and optical studies of hybrid perovskite materials for solar cell and light emitting devices - Wang, Tianhui (Nanyang Technological University, 2021)
Perovskite matrials recently generate great attention due to its perfect performance in solar cell and light emitting devices. It has many advantages such as high carrier mobility, tunable band gap and easy fabrication. Two-dimensional (2D) perovskites have unique properties due to the electron confinement effect and exiton-phonon coupling. The interaction between the centre molecule and surrounding cage has great influences on the molecular dynamics, phase stability, and even phase transformations. Thus, it is important to figure out the relationship between its structure changes and optical properties. The vibration mode in various temperature is significant to analyse in order to improve their stability. The Ruddlesden−Popper structure for 2D perovskite perform distinct vibration mode directionally, for both organic part and inorganic octahedral layer. In this report, the optical properties of of (BA)2PbI4 (BA is butylammonium) and (PEA)2PbI4 (PEA is phenylethylammonium) are analysed in temperature ranged from 303K to 80K in terms of Raman scattering, photoluminiscense and Optical Absorption. It is found that (BA)2PbI4 went through great phase transition at around 203K while (PEA)2PbI4 does not change much. (PEA)2PbI4 is found to be more stable than (BA)2PbI4 due to stronger π- π interactions between the PEA molecules, while between the BA molecules the van der Waals forces are weak. Decrease in temperature strengthens the hydrogen bonding in both samples, as reflected in Raman spectroscopy.